Endovascular Aortic Repair : Current Techniques with Fenestrated, Branched and Parallel Stent-Grafts - Oderich, Gustavo S. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, state-of-the art review of complex endovascular aortic techniques. It will serve as a valuable resource for vascular and cardiovascular surgeons, interventionalists, cardiologists, clinicians, bioengineers and researchers with an interest in complex aortic diseases. The book reviews imaging modalities, diagnostic work up and novel endovascular approaches. Technical aspects are provided by experts in the field, with over 600 illustrations and photographs of key steps for each type of procedure. Results of epidemiologic studies and national databases are summarized, as well as large institutional experiences. An evidence-based approach is used for recommendations regarding best therapies. Other highlights of this unique text include: A new, state-of-the-art review on fenestrated, branched and parallel stent-graft techniques from procedure planning to stent design and implantation. A text dedicated to a topic that has been increasingly recognized by vascular specialists as a priority area in aortic management. An updated overview of current designs and future developments. Special attention to technical details of the procedures with use of illustrations. Technical tips on how to get out of problems during these challenging procedures. Endovascular Aortic Repair: Current Techniques with Fenestrated, Branched and Parallel Stent-Grafts will serve as a very useful resource for physicians and researchers dealing with and interested in complex aortic diseases. It will provide a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up to date scientific and clinical information. - Resumé vydavatel
Keywords: cévní chirurgie; kardiochirurgie; aorta; stenty; vascular surgery; cardiac surgery; stents (surgery); elektronické knihy; kolektivní monografie; electronic books; collective monographs